The political economy of stalinism : - Gregory, Paul R. (Cambridge University Press, 2004)
This book uses the formerly secret Soviet state and Communist Party archives to describe the creation and operations of the Soviet administrative command system, how and why the Soviet administrative command system operated and failed. Although the command system was the most significant human experiment of the twentieth century, its basic contradictions and inherent flaws would re-surface if it were to be repeated.